2017
DOI: 10.1016/j.socscimed.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Between a rock and a hard place: Economic expansion and social responsibility in UK media discourses on the global alcohol industry

Abstract: Context Transnational alcohol corporations (TACs) employ a range of strategies to achieve their business objectives, including attempts to frame perceptions of their activities in media debates. TACs aim to achieve a favourable regulatory environment by presenting themselves as socially responsible actors. However, the need to secure financial investment means they must also emphasise their potential for growth. This article investigates tensions between these objectives in coverage of the global alcohol indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Overall, our findings add to the literature on the contradictions that exist in the discourses of the AI, 79 whereby the industry claims that it is supporting public health and "Nudging for Good," 80,81 while simultaneously, through its CSR bodies, using dark nudges that are aligned with commercial rather than public health goals. Its key approach involves presenting health information, but subverting it with a range of dark nudges and sludge.…”
Section: (Sabmiller)supporting
confidence: 54%
“…Overall, our findings add to the literature on the contradictions that exist in the discourses of the AI, 79 whereby the industry claims that it is supporting public health and "Nudging for Good," 80,81 while simultaneously, through its CSR bodies, using dark nudges that are aligned with commercial rather than public health goals. Its key approach involves presenting health information, but subverting it with a range of dark nudges and sludge.…”
Section: (Sabmiller)supporting
confidence: 54%
“…Concerning the SDIL, a media analysis starting a year before the announcement of the policy suggested that articles supportive of SSB taxation (23.5%) outnumbered those that were oppositional (14.2%) [ 28 ] and that arguments underpinning proponents and opponents of the SDIL were broadly consistent with those used within the alcohol and tobacco industry [ 29 ]. While most of the research examining media representations of industry and their discursive strategies is focused on message framing [ 30 ], there is evidence that industry messaging can shift depending on the audience, with conflicting or contradictory debates and responses to regulation [ 31 , 32 ]. Therefore, examining industry reactions throughout policy development and implementation processes could offer novel insights into how industry messaging evolves in a changing political landscape over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, this paper investigates how alcohol issues are covered in the news media by examining newspapers. It engages with the growing literature on this subject, which has investigated news media coverage of minimum pricing [ 5 , 6 , 7 , 8 ], alcohol use [ 9 ], the alcohol industry itself [ 10 ], alcohol policy and education [ 11 , 12 ], alcohol advertising [ 13 ], alcohol in ethnic and racial minority newspapers [ 14 ], as well as specific pieces of alcohol-related legislation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%